2008
DOI: 10.3394/0380-1330-34.4.581
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and Fatty Acid Content of Lake Michigan Chinook Salmon

Abstract: Nutritional status of Lake Michigan Chinook salmon (Oncorhynchus tshawytscha) is inadequately documented. An investigation was conducted to determine muscle and liver thiamine content and whole body fatty acid composition in small, medium and large Chinook salmon. Muscle and liver thiamine concentrations were highest in small salmon, and tended to decrease with increasing fish size. Muscle thiamine was higher in fall than spring in large salmon. The high percentage of Chinook salmon (24-32% in fall and 58-71% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…The liver is the site of many energetically expensive processes and thus has a high requirement for thiamine. In those cases of suspected thiamine shortage in salmonines, it has been suggested that the muscle to liver thiamine ratio is reduced, indicating preferential retention of the vitamin in liver (Honeyfield et al , 2008). In this context, liver thiamine levels were investigated in one Lake Ontario spawning population, that of the Napanee River.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the site of many energetically expensive processes and thus has a high requirement for thiamine. In those cases of suspected thiamine shortage in salmonines, it has been suggested that the muscle to liver thiamine ratio is reduced, indicating preferential retention of the vitamin in liver (Honeyfield et al , 2008). In this context, liver thiamine levels were investigated in one Lake Ontario spawning population, that of the Napanee River.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting mean thiamine (nmol) content for the eight size-classes (e.g., 200-1,000 mm) was related to the size-class midpoint (mm), and the resulting variation was examined as above. This procedure assumed that (1) muscle thiamine represented the mean thiamine concentration for the entire body given that muscle comprises the bulk of total body weight, and (2) while other tissues, like liver, have a higher thiamine concentration than muscle (Honeyfield et al 2008a), they represent a relatively small proportion of total body weight (Thorarisson et al 1994). This procedure also assumed that muscle as a proportion of total body weight remained unchanged over the same length categories examined.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the thiamine content of adult Chinook Salmon related to size have been documented for Lake Michigan, although the relationship with diet and thiamine dynamics in juveniles remains unclear. For adult Chinook Salmon in Lake Michigan, a negative association was reported between dorsal muscle thiamine concentration and fish size (Honeyfield et al 2008a); thiamine levels in small Chinook Salmon (<490 mm) were almost twofold higher than those in large individuals (>700 mm). Honeyfield et al (2008a) contended that the most likely reason for the differential in muscle thiamine concentrations between small and large fish was that smaller fish were eating a more diverse diet, but no data were provided to support this claim.…”
mentioning
confidence: 95%
See 2 more Smart Citations